Molecular identification, genotyping and phylogenetic analysis of Ixodes and Rhipicephalus ticks and their associated spotted fever group Rickettsia species from a single location in northern Tunisia - Kratou, Myriam; Belkahia, Hanène; Selmi, Rachid; Abdallah, Meriam Ben; Tayh, Ghassan; Messadi, Lilia; Ben Said, Mourad (Frontiers in Microbiology, 2025)
IntroductionTicks and their associated spotted fever group Rickettsia (SFGR) represent an emerging zoonotic risk in Tunisia, where data on tick species distribution and pathogen prevalence remain limited. This study specifically aimed to investigate the diversity and phylogeny of Ixodes and Rhipicephalus tick species and to identify and genetically characterize their associated SFGR species in northwestern Tunisia.MethodsTick sampling was conducted over a five-month period, from November 2022 to March 2023, in the Jouza district, Beja Governorate, northern Tunisia. A total of 236 ticks were collected both from vegetation using flag-dragging and manually from a red fox (Vulpes vulpes) carcass encountered opportunistically in the field. Tick species were morphologically identified and confirmed by Sanger sequencing of the mitochondrial 16S rRNA gene. Rickettsia detection was performed by nested PCR targeting the ompB gene, followed by species-level identification through sequencing of ompA and gltA partial sequences. Phylogenetic analyses were conducted to assess genetic relationships. Additionally, chi-square tests were used to assess differences in infection rates between tick species, life stages, and collection sources.ResultsTicks belonged to the Ixodes ricinus complex (Ix. ricinus and Ix. inopinatus), Ix. hexagonus, and the Rhipicephalus sanguineus sensu lato complex (Rh. sanguineus sensu strict and Rh. rutilus) have been identified. Twelve and ten genotypes were recorded from 45 and 59 partial 16S rRNA mitochondrial sequences isolated from Ix. ricinus and Ix. inopinatus, respectively. Additionally, one genotype was recorded from five Rh. rutilus specimens, and four genotypes were detected among 23 Rh. sanguineus (temperate lineage) individuals. Overall, 52.1% of ticks tested positive for Rickettsia spp., with significantly higher infection rates in Ix. ricinus (75.6%, p < 0.001) and Ix. inopinatus (67.4%, p < 0.01) compared to the Rhipicephalus group (37.2%) and Ix. hexagonus, which tested negative. Three Rickettsia species were identified: R. monacensis and R. helvetica in the Ix. ricinus complex (including one co-infection), and R. massiliae exclusively in Rhipicephalus ticks. Moreover, phylogenetic analysis revealed that our tick isolates and associated Rickettsia spp. from questing ticks and the red fox clustered primarily with those from other North African and Southern European countries, suggesting trans-Mediterranean strain circulation and a potential link to wildlife reservoirs.ConclusionThese findings enhance our understanding of tick and SFGR diversity in Tunisia and underscores the zoonotic risks from co-circulating Rickettsia species in shared environments. The high infection rates in Ix. ricinus and Ix. inopinatus call for improved national tick surveillance. Public health implications include the need to consider tick-borne rickettsioses in unexplained febrile illness diagnoses. Future studies should assess infection status in hosts, explore seasonal tick dynamics, and evaluate environmental factors affecting Rickettsia transmission.